Piece-By-Piece Shape-Morphing: Engineering Compatible Auxetic and Non-Auxetic Lattices to Improve Soft Robot Performance in Confined Spaces - Dikici, Yusuf; Jiang, Hao; Li, Bo; Daltorio, Kathryn A.; Akkus, Ozan (Wiley-V C H Verlag Gmbh, 2022)
Shape-morphing capabilities of metamaterials can be expanded by developing approaches that enable the integration of different types of cellular structures. Herein, a rational material design process is presented that fits together auxetic (anti-tetrachiral) and non-auxetic (the novel nodal honeycomb) lattice structures with a shared grid of nodes to obtain desired values of Poisson's ratios and Young's moduli. Through this scheme, deformation properties can be easily set piece by piece and 3D printed in useful combinations. For example, such nodally integrated tubular lattice structures undergo worm-like peristalsis or snake-like undulations that result in faster speeds than the monophasic counterpart in narrow channels and in wider channels, respectively. In a certain scenario, the worm-like hybrid metamaterial structure traverses between confined spaces that are otherwise impassable for the isotropic variant. These deformation mechanisms allow us to design shape-morphing structures into customizable soft robot skins that have improved performance in confined spaces. The presented analytical material design approach can make metamaterials more accessible for applications not only in soft robotics but also in medical devices or consumer products.
Keywords: Auxetics; Lattice Structures; Mechanical Metamaterials; Shape Morphing